1999
DOI: 10.1046/j.1460-9568.1999.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

GABAB‐receptor splice variants GB1a and GB1b in rat brain: developmental regulation, cellular distribution and extrasynaptic localization

Abstract: GABAB (gamma-aminobutyric acid)-receptors have been implicated in central nervous system (CNS) functions, e.g. cognition and pain perception, and dysfunctions including spasticity and absence epilepsy. To permit an analysis of the two known GABAB-receptor splice variants GABAB-R1a (GB1a) and GABAB-R1b (GB1b), their distribution pattern has been differentiated in the rat brain, using Western blotting and immunohistochemistry with isoform-specific antisera. During postnatal maturation, the expression of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
198
0
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(242 citation statements)
references
References 37 publications
38
198
0
6
Order By: Relevance
“…Immunocytochemical studies have revealed that GABAB receptors are distributed throughout the striatum, hippocampus, DG, hypothalamus, tectum, cerebellum, brainstem and spinal cord of rat (Fritschy et al, 1999;Margeta-Mitrovic et al, 1999;Calver et al, 2000). In the present study, we found that i.c.v.…”
Section: Discussionsupporting
confidence: 60%
“…Immunocytochemical studies have revealed that GABAB receptors are distributed throughout the striatum, hippocampus, DG, hypothalamus, tectum, cerebellum, brainstem and spinal cord of rat (Fritschy et al, 1999;Margeta-Mitrovic et al, 1999;Calver et al, 2000). In the present study, we found that i.c.v.…”
Section: Discussionsupporting
confidence: 60%
“…To gain the first insights into the mechanisms involved in endocytosis of GABA B receptors, we expressed in HEK 293 cells the GABA B1b /GABA B2 combination, which is the most abundant GABA B receptor subtype in the adult brain (10,11). Heterologous expression of receptors was chosen, since it is a robust, easy to manipulate and to evaluate system.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway may be important during development of the nervous system. GABA B receptors are highly regulated during development with changes occurring in the levels of the splice variants and subunits (38)(39)(40). Changes in the relative levels of GABA B -R1͞GABA B -R2 may alter the ability of the GABA B receptor to interact with transcription factors and thereby regulate changes in gene expression during development.…”
Section: Discussionmentioning
confidence: 99%